Rancang Bangun Website Untuk Layanan Jasa Kuliner - Prabowo, Sigit, Gunawan Ariyanto,ST. M. Compt Sc., Ph.D, Umi Fadlilah, ST. M. Eng (2016)
Culinary business which today is growing rapidly and promises to provide benefits in a relatively short time also allows for the development of enterprises. Culinary business is currently booming, one of which is Bebek Goreng H. Slamet. It is undeniable that the primary key of the restaurant business is the level of customer satisfaction (customer satisfaction level). So expect from management in order to provide easiness to customers. In this study, using a technology that can provide solutions to overcome the problems more efficiently. By using Web Services-based applications Soap in communication between the client and the server, which will display related information between customers and buyers and can promote the culinary business that is more developed. Use of Web Service-based Soap in the culinary business simulation applications can make it easier for the client to update the data if the admin menu to make changes, but it also facilitate in making the report because Admin client is connected with all that preparation of reports can be done effectively and efficiently. Keywords: Client, Server, Simulation, Soap, Web Service